Marketing strategy a decision-focused approach - Walker, Orville C.; Mullins, John W. (McGraw-Hill/Irwin, 2014)
Covers the concepts and theories of creating and implementing a marketing strategy and offers a focus on the strategic planning process and marketing's cross/inter-functional relationships. This text distinguishes itself from competitors by maintaining a strong approach to strategic decision making.